2017
DOI: 10.1021/acsbiomaterials.7b00266
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel Modulus Affects Proliferation Rate and Pluripotency of Human Mesenchymal Stem Cells Grown in Three-Dimensional Culture

Abstract: Hydrogels have been used extensively with various cell types in three-dimensional (3D) culture, including with human mesenchymal stem cells (hMSCs). Here, we report on the use of poly­(ethylene glycol) (PEG)-conjugated fibrinogen hydrogels to grow bone marrow-derived hMSCs in 3D culture. The initial modulus of the PEG-fibrinogen (PF) hydrogels was varied to study the influence of the stiffness on the proliferation response of the cells growing within. Shear rheology was used to quantify the changes to the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 79 publications
(156 reference statements)
5
34
0
Order By: Relevance
“…Crucially, even before printing, the hydrogel moduli affect the cell viability when encapsulated. For example, low moduli hydrogels (<1 kPa) can often provide a better environment for cells to attach, expand and proliferate [ 72 , 73 ]. Physically stronger gels can be loaded with cells with the help of mechanical methods (mixing, centrifugation or vortexing) ensuring high printing fidelity, nevertheless cell encapsulation still remains a crucial and unresolved issue.…”
Section: The Challenge Of Cell Printing For Tissue Engineeringmentioning
confidence: 99%
“…Crucially, even before printing, the hydrogel moduli affect the cell viability when encapsulated. For example, low moduli hydrogels (<1 kPa) can often provide a better environment for cells to attach, expand and proliferate [ 72 , 73 ]. Physically stronger gels can be loaded with cells with the help of mechanical methods (mixing, centrifugation or vortexing) ensuring high printing fidelity, nevertheless cell encapsulation still remains a crucial and unresolved issue.…”
Section: The Challenge Of Cell Printing For Tissue Engineeringmentioning
confidence: 99%
“…Researchers have also taken advantage of the ability of hydrogels to swell or shrink in response to external stimuli (e.g., pH, temperature) to develop biosensors for the detection of biomolecules [4,5]. Additionally, their highly porous and hydrated polymer structure mimics the extracellular cellular matrix and renders them highly suitable for in vitro cell culture, and several studies have demonstrated the successful use of hydrogels to encapsulate mammalian cells in a 3D physiological-like environment and develop in vitro models of cell proliferation, migration, and differentiation [6][7][8][9][10]. However, hydrogels have poor mechanical strength, which limits their broad applicability for tissue engineering [11].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the benign character of photopolymerization, living cells can be easily encapsulated and imaged in these materials, that can also be fashioned in the form of microparticles or spheroid/microspheres . These PEGylated fibrinogen gels have been employed in a variety of in vitro models, for example, including pluripotency maintenance (human mesenchymal stem cells) or neural growth neural outgrowth, and have been applied in vivo for BMP‐2 stimulated bone repair, for the generation of skeletal muscles from encapsulated mesangioblasts, for the regeneration of sciatic nerve, or for myocardial regeneration (no cell encapsulated) after infarction …”
Section: Fibrin As An Artificial Extracellular Matrixmentioning
confidence: 99%